The role of social support and psychological capital in college students' physical exercise behavior: a mediation analysis - Xiong, You; Si, Juncheng; Huang, Zhan; Ouyang, Junjie; Ma, Shuai; Huang, Yao; Huang, Xiaoling (Frontiers in Psychology, 2025)
BackgroundThe physical exercise behavior of college students is closely related to their physical and mental health. Research has shown that social support and psychological capital are related to college students' physical exercise behavior, but their correlation needs further exploration.ObjectivesThis study seeks to investigate the relationship between social support, psychological capital and university students' physical exercise behavior, with a further in-depth analysis of the mediating roles played by psychological capital within this dynamic.MethodsUsing cluster sampling, we surveyed 359 college students in Southwest University, employing the Sports Activity Level Scale (SALS), the Positive Psychological Capital Questionnaire (PPCQ), the Social Support Scale (SSS). Data were analyzed using SPSS 26.0 and STATA 17.0, and common method bias was tested using Harman's single-factor test. The significance of the mediation effects was tested using the Kohler, Karlson, and Breen (KHB).Results(1) Peer support (P < 0.01), teacher support (P < 0.01), family support (P < 0.05), and psychological capital (P < 0.05) are significantly correlated with college students‘ physical exercise behavior. (2) Social support positively correlates with the positive psychological capital of college students (P < 0.01). The indirect effects of peer, teacher, and family support on college students' physical exercise behavior through psychological capital account for 87.34%, 36.95%, and 30.69% of the total effect. (3) According to the regression coefficient, social support is ranked as peer support (0.11), teacher support (0.10), and family support (0.09).ConclusionSocial support shows a positive association with college students' physical exercise behavior and also demonstrates a significant correlation with it through psychological capital. Teacher support in the school living environment is equally important, and future research should focus on developing the role of family support.